Electrochemical characteristics of coated steel with poly(N-methyl pyrrole) synthesized in presence of ZnO Nanoparticles - Mahmoudian, M.R.; Zak, A.K.; Alias, Y.; Basirun, Wan Jefrey (Elsevier, 2011)
Electrodeposition of ZnTe thin films by controlled potential method from aqueous solutions on ITO were done to investigate characteristics suitable as a window material in solar cells technology. The influence deposition of potential towards the Zn:Te ratio and the crystallinity are discussed. The electrodeposited films were investigated by using X-Ray Diffraction and Energy Dispersive Analysis of X-Ray. The Te content decreases at higher deposition potentials. © (2011) Trans Tech Publications, Switzerland.